Addition of pomace powder of Manjari Medika grapes (Vitis vinifera) improves nutraceutical and sensory properties of wheat bread (Current Horticulture, 2024)
The baking conditions were standardized to replace wheat flour by pomace powder of grapes (Vitisvinifera) of Manjari Medika as T2, T3, T4 and T5 and compared with control (T1). Replacement of wheat flour by pomace powder tremendously improved nutritional and functional properties of breads compared with the control. The breads with pomace powered resulted in higher mineral contents. Available anthocyanins in pomace powder influenced colour intensity of breads. Evaluation of breads based on sensory properties, 5% replacement was found with maximum acceptance level followed by 10%. While 15 and 20% replacement were observed with lower score than the control. All levels of pomace powder scored better than the control for flavour. Thus, it is concluded that 10% replacement of wheat flour by pomace powder of Manjari Medika is well acceptable and can be adopted by bakery industries in bread-making.
Keywords: Wine; Juice; Baking; Functional properties; Natraceutical; Sensory